Analisis faktor penyebab kurangnya rasa percaya diri siswa dalam belajar di SMP Islam Baiturrahim Jambi - Simar; Muhammad Ferdiansyah; Zubaidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to find out and describe in depth the factors causing students' lack of self-confidence in learning at SMP Islam Baiturrahim Jambi. This study uses a qualitative research method with a descriptive case study approach. The subjects of the study were two grade IX students based on the results of the questionnaire who had low levels of self-confidence. Data collection techniques through interviews, observations, documentation, with data analysis through data reduction, data presentation. The results of the study indicate that the factors causing students' lack of self-confidence in the learning process are caused by internal and external factors. Internal factors are dominant factors, including negative self-concepts, low self-esteem, and previous negative experiences. Students tend to feel incapable, afraid of failure, and doubt their own potential, so they are reluctant to actively participate in the learning process. In addition, external factors also contribute to students' lack of self-confidence in learning, namely, a less supportive learning environment and parenting patterns that lack communication and emotional support, this situation causes students to not get space to grow self-confidence both in the family and school environments. Keywords: Lack of self-confidence; causal factors; students